Improved LC-MSn characterization of hydroxycinnamic acid derivatives and flavonols in different commercial mate (Ilex paraguariensis) brands. Quantification of polyphenols, methylxanthines, and antioxidant activity. (15th February 2018) - Mateos, Raquel; Baeza, Gema; Sarriá, Beatriz; Bravo, Laura
Highlights: Fifty-eight phenolic compounds and two methylxanthines were identified in yerba mate. Caffeoyl-2, 7-anhydro-3-deoxy-2-octulopyranosonic acid isomers are identified for the first time. First identification of 4-sinapoylquinic and other cinnamoylquinic and shikimic acids in mate. Hydroxycinnamic acid derivatives and flavonols comprise 90% and 10% of mate phenols, respectively. The antioxidant capacity of mate is mainly associated to its polyphenol content. Abstract: Yerba mate is a beverage rich in bioactive compounds popular in South America. Polyphenols and methylxanthines were qualitatively and quantitatively analyzed in four commercial brands of yerba mate, as well as the antioxidant capacity of the beverages. Using LC/MS n analysis, 58 polyphenols were observed of which 4-sinapoylquinic acid, di- and tri-methoxycinnamoylquinic acids, two isomers of trimethoxycinnamoylshikimic acid and four isomers of caffeoyl-2, 7-anhydro-3-deoxy-2-octulopyranosonic acid were identified for the first time in mate. Additionally, 46 polyphenols and 2 methylxanthines were quantified by HPLC-DAD. Hydroxycinnamic acid derivatives and flavonols comprised 90% and 10% of mate phenols, respectively, 3-caffeoylquinic (26.8–28.8%), 5-caffeoylquinic (21.1–22.4%), 4-caffeoylquinic (12.6–14.2%) and 3, 5-dicaffeoylquinic acids (9.5–11.3%) along with rutin (7.1–7.8%) were the most abundant polyphenols, whereas caffeine was the main methylxanthine (90%). Ilex paraguariensis is an important source of polyphenols with moderate methylxanthines content; therefore its high antioxidant capacity was mainly associated to its polyphenolic composition.